Antiviral Susceptibility of Highly Pathogenic Avian Influenza A(H5N1) Viruses Circulating Globally in 2022–2023 - Andreev, Konstantin; Jones, Jeremy C; Seiler, Patrick; Kandeil, Ahmed; Turner, Jasmine C M; Barman, Subrata; Rubrum, Adam M; Webby, Richard J; Govorkova, Elena A (The Journal of infectious diseases, 2024)
Abstract The antiviral susceptibility of currently circulating (2022–2023) highly pathogenic avian influenza (HPAI) A(H5N1) viruses was assessed by genotypic and phenotypic approaches. The frequency was low for neuraminidase (NA) and polymerase acidic (PA) substitutions associated with reduced inhibition by NA inhibitors (21/2698, 0.78%) or the PA inhibitor baloxavir (14/2600, 0.54%). Phenotypic testing of 22 clade 2.3.2.1a and 2.3.4.4b viruses revealed broad susceptibility to NA inhibitors and baloxavir for a conclusion that most contemporary HPAI A(H5N1) viruses retain susceptibility to antiviral drugs. Novel NA-K432E and NA-T438I substitutions (N2 numbering) were identified at elevated frequencies (104/2698, 3.85%) and caused reduced zanamivir and peramivir inhibition.